The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.esxm.2019.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Do Urologists Really Recognize the Association Between Erectile Dysfunction and Cardiovascular Disease?

Abstract: Introduction: Erectile dysfunction (ED) and cardiovascular diseases (CVDs) share many common risk factors. ED could be a strong independent predictive factor of CVDs. Furthermore, the treatment of ED had been shown to be beneficial for cardiovascular diseases. However, the association between ED and CVDs has been reported scarcely in the literature. Aim: To investigate urologists' perception, diagnosis, and treatment of CVDs in patients with ED. Methods: The study was conducted as a prospective study from Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The acceptance value (AV) was determined using Equation (3). AV = (X − M) + KS (3) where X represents the average drug content, S represents the standard deviation and K represents a constant that is either 2.4 for 10 dosage units or 2.0 for 30 dosage units. If 98.5% ≤ X ≤ 101.5%; M = X, if X < 98.5%; M = 98.5%, if X > 101.5%; M = 101.5%.…”
Section: Flowabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The acceptance value (AV) was determined using Equation (3). AV = (X − M) + KS (3) where X represents the average drug content, S represents the standard deviation and K represents a constant that is either 2.4 for 10 dosage units or 2.0 for 30 dosage units. If 98.5% ≤ X ≤ 101.5%; M = X, if X < 98.5%; M = 98.5%, if X > 101.5%; M = 101.5%.…”
Section: Flowabilitymentioning
confidence: 99%
“…Globally, the prevalence of ED is rated to be roughly 322 million cases by 2025 [2]. A recent study indicated that, 52% of men between the ages of 40 and 70 years suffered from ED [3]. It causes deep negative influence on an individual's social life and prosperity [1].…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors are common to both ED and CVD ( 40 , 41 ). It is important to recognize the connection between ED and CVD in order to effectively prevent and treat both conditions ( 42 , 43 ). Additionally, ED significantly impacts patients’ quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Many cardiologists recognize the relationship between ED and CVD, but many people believe that ED is a natural aging process rather than a disease. 20 Therefore, cardiologists do not pay enough attention to the ED in the clinic. However, the effect of ED on the quality of life of patients is very significant.…”
Section: Discussionmentioning
confidence: 99%